The Implementation of Norms for Liturgical Songs and Musical Instruments by Catholic Youth in the St. Raphael Sub-Parish, Saitnihuta - Lumban Tobing, Rhaffael Sebastian; Fajariyanto, Tri Chandra (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This study explores the implementation of liturgical music norms by Catholic Youth (Orang Muda Katolik/OMK) in the St. Raphael Sub-Parish, Saitnihuta. The research aims to examine the extent to which OMK participate in liturgical music ministry in accordance with the principles established by the Catholic Church, particularly regarding the use of liturgical songs and musical instruments. Employing a qualitative descriptive method, data were collected through interviews, observations, and documentation. The findings reveal that OMK show commendable enthusiasm and active involvement in liturgical celebrations by singing hymns from official Church songbooks such as Puji Syukur and by accompanying the liturgy with instruments like guitars, cajons, and keyboards. While this reflects a genuine commitment to serve, it also exposes a lack of structured guidance and theological understanding related to the use of music in the liturgy. Many OMK rely on imitation and personal experience in selecting songs and instruments, often prioritizing the creation of a lively atmosphere rather than enhancing the sacredness of the liturgy. Moreover, the absence of traditional musical instruments and limited liturgical catechesis hinder the proper application of inculturation principles. This study underscores the urgent need for structured formation programs and official liturgical music guidelines to support OMK. With proper mentoring, the creativity and zeal of young people can be nurtured to align with the Church’s vision of sacred, beautiful, and appropriate liturgical music—thus enabling them to become true ministers of prayer who deepen the community’s encounter with the mystery of Christ.